2009
DOI: 10.1016/j.virol.2008.11.035
|View full text |Cite
|
Sign up to set email alerts
|

Characterizations of four monoclonal antibodies against M2 protein ectodomain of influenza A virus

Abstract: M2 protein of influenza A virus has been implicated as a target for vaccines with broad cross-strain coverage. Studies in small animal models have shown that antibody responses induced by 23-mer M2 peptide vaccines can provide protection against influenza A virus challenge. To study antiviral mechanisms of Merck M2-OMPC conjugate vaccine, we generated and characterized four M2 peptide-specific monoclonal antibodies (mAbs). Here we demonstrated that the protection by our M2 mAbs is independent of NK-mediated ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
57
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 29 publications
7
57
0
1
Order By: Relevance
“…Hence, the specificity and affinity of the purified subclasses as well as their purity may have been different adding further variables to this published report. In addition, Fu et al [30] also reported some protective capacity of M2e-specific IgG1 antibodies. However, there was no proper comparison between IgG1 and IgG2a/c antibodies made.…”
Section: Resultsmentioning
confidence: 95%
“…Hence, the specificity and affinity of the purified subclasses as well as their purity may have been different adding further variables to this published report. In addition, Fu et al [30] also reported some protective capacity of M2e-specific IgG1 antibodies. However, there was no proper comparison between IgG1 and IgG2a/c antibodies made.…”
Section: Resultsmentioning
confidence: 95%
“…In contrast to the apparently uniform antibody response to M2e in naturally infected or vaccinated humans, mice immunized with M2e-derived peptides produced antibodies with a range of specificities within M2e, including the conserved N terminus and also downstream regions (15). It is tempting to speculate that the human immune system has evolved a humoral response that exclusively targets the highly conserved N-terminal segment of M2e rather than the more divergent, and thus less sustainably protective, downstream sites.…”
Section: Resultsmentioning
confidence: 98%
“…Monoclonal antibodies to M2e have been shown to be protective in vivo (13)(14)(15)(16)(17), and several groups have demonstrated protection against infection with vaccine strategies based on M2e (18)(19)(20)(21)(22)(23). In these cases, purified M2 protein or peptides derived from M2e sequence have been used as immunogens to generate antiM2e antibodies in animals or as vaccine candidates.…”
mentioning
confidence: 99%
“…Jegerlehner et al (15) proposed an important role for NK-mediated Ab-dependent cytotoxicity in acquired anti-M2e immunity. However, two recent studies concluded that NK cells are not essential for protection by anti-M2e IgG or following vaccination with M2 expression vectors (16,43). All three studies made use of Ab administration to eliminate NK and NKT cells, either anti-NK1.1 (43) or antiasialo-GM1 (15,16), but used different mouse strains [C57BL/6 (15,43) and BALB/c (16) mice] and different influenza virus challenge strains.…”
Section: Discussionmentioning
confidence: 99%